2017
DOI: 10.1113/jp272772
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ tunnelling through the ER lumen as a mechanism for delivering Ca2+ entering via store‐operated Ca2+ channels to specific target sites

Abstract: Ca2+ signalling is perhaps the most universal and versatile mechanism regulating a wide range of cellular processes. Because of the many different calcium‐binding proteins distributed throughout cells, signalling precision requires localized rises in the cytosolic Ca2+ concentration. In electrically non‐excitable cells, for example epithelial cells, this is achieved by primary release of Ca2+ from the endoplasmic reticulum via Ca2+ release channels placed close to the physiological target. Because any rise in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 113 publications
0
48
0
1
Order By: Relevance
“…Together, these results showed that the expression of IP 3 R3 also could regulate SOCE in HEK cells. It is known that SOCE-mediating CRAC channels, SERCA and IP 3 Rs are functionally coupled under physiological conditions [24][25][26]43]. Our results thus added a new aspect of couplings among Ca 2+ handling machineries.…”
Section: Expression Of Ip 3 R3 Restored the Reduced Orai1 Protein Levmentioning
confidence: 54%
“…Together, these results showed that the expression of IP 3 R3 also could regulate SOCE in HEK cells. It is known that SOCE-mediating CRAC channels, SERCA and IP 3 Rs are functionally coupled under physiological conditions [24][25][26]43]. Our results thus added a new aspect of couplings among Ca 2+ handling machineries.…”
Section: Expression Of Ip 3 R3 Restored the Reduced Orai1 Protein Levmentioning
confidence: 54%
“…Ca 2+ signalling studies on isolated pancreatic acinar cells (PACs) or small acinar cell clusters have led to a detailed understanding of the mechanisms underlying the primary intracellular Ca 2+ release elicited by physiological and pathological agents as well as the subsequent opening of store-operated Ca 2+ channels in the plasma membrane that accounts for the secondary Ca 2+ entry from the extracellular solution Petersen et al 2017). Physiological, short-lasting and repetitive local Ca 2+ signals control acinar fluid and enzyme secretion (Petersen, 1992;, whereas sustained global elevations of the cytosolic Ca 2+ concentration ([Ca 2+ ] i ), elicited by pathological agents, play a key role in the development of the acinar cell damage and death leading to acute pancreatitis (AP) (Gerasimenko et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we investigate the linear stability of the synchronous network state as the strength of Ca 2+ diffusion is varied. Due to different intracellular morphologies and biochemical compositions, Ca 2+ generally diffuses more quickly in the cytosol than in the SR (but see Petersen et al (2017) for a different view). While diffusion of free Ca 2+ in the cytosol has been estimated to be 223 μm 2 s −1 (Allbritton et al 1992), Ca 2+ buffers reduce this value substantially (Smith et al 1996;Wagner and Keizer 1994).…”
Section: Introductionmentioning
confidence: 99%